2020
DOI: 10.1021/acsaem.0c02298
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interface Stability of Si Anodes by Mg Coating in Li-Ion Batteries

Abstract: Silicon (Si) is a promising anode material for high-energy-density lithium-ion batteries (LIBs), but its short calendar life and poor cycling performance prevent its large-scale adoption. Introducing magnesium (Mg) salt into the electrolyte has been recently shown to form a ternary Li−Mg−Si Zintl phase upon lithiation of Si and improve the cycling performance. However, the ternary Zintl phase formation mechanism and its impact on the solid electrolyte interphase (SEI) are not yet well understood. Here, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…88,89 Moreover, it is reported that FEC exhibits a higher affinity towards the silicon surface than EC, and forms an ordered, up-right orientation, which may promote SEI formation and Li diffusion. 90,91 Most recently, artificial surface coating with the appropriate binder, 92 oxide layer, 93 and Mg metal 94 have been used to alter the interfacial interactions and reactions between the Si anode and electrolytes for achieving a stable SEI that minimizes side reactions and sustains efficient cycling. Finally, water contamination has been reportedly to causes detrimental parasitic reactions that affects the formation, evolution, and properties of the SEI.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…88,89 Moreover, it is reported that FEC exhibits a higher affinity towards the silicon surface than EC, and forms an ordered, up-right orientation, which may promote SEI formation and Li diffusion. 90,91 Most recently, artificial surface coating with the appropriate binder, 92 oxide layer, 93 and Mg metal 94 have been used to alter the interfacial interactions and reactions between the Si anode and electrolytes for achieving a stable SEI that minimizes side reactions and sustains efficient cycling. Finally, water contamination has been reportedly to causes detrimental parasitic reactions that affects the formation, evolution, and properties of the SEI.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…It has been demonstrated that the electrochemical performance of silicon can be effectively improved by blocking the direct contact between silicon and electrolyte through surface coating modification. In addition to the coating of carbon materials, there are many other coating materials, such as metals, [105–112] metal silicide, [113–115] metal oxides, [116–127] metal sulfides, [37,128–134] silicon oxides, [135–145] and others [146–150] . The coating can exist in a tough or flexible form to buffer the volume expansion of silicon during cycling.…”
Section: Si/metallic or Nonmetallic Compositesmentioning
confidence: 99%
“…It was recently shown that the introduction of Mg salts can lead to the formation of ternary Li‐Mg‐Si Zintl phases during lithiation of Si, resulting in improved cycling performance. For a clearer understanding of the formation mechanism of ternary Zintl phase and its influence on SEI, Li et al [109] . prepared silicon thin films coated with magnesium layers as model electrodes (Figure 18a).…”
Section: Si/metallic or Nonmetallic Compositesmentioning
confidence: 99%
“…Table 1 displays the electrochemical performance of different Si-based electrode materials [26,28,[64][65][66][67][68][69][70]. The as-synthesized BM-SFG anode presents relatively excellent Li storage performance, which is better than that of many reported Si-based composites.…”
Section: Comparison Of Electrochemical Performance Of Li-ion Batteriesmentioning
confidence: 99%